Association of temperature and rainfall with Aedes mosquito population in 17th college of Universiti Putra Malaysia - Gopalsamy, Banulata; Saiful Yazan, Latifah; Abdul Razak, Nissa Nabila; Man, Mustafa (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: Dengue is an arboviral disease affecting many tropical and subtropical regions. Statistics in Malaysia show that a cumulative of 57,627 number of DF cases with 94 cumulative number of deaths have occurred until July 8th 2020. Weather affects Aedes mosquito population and dengue incidence through the breeding behaviour of mosquitoes. This study aims to evaluate the association of temperature and rainfall with Aedes mosquito population in the 17th College, Universiti Putra Malaysia (UPM) and also to evaluate the accuracy of mobile ‘AedesTech’ automated counting application. Methods: Aedes Mosquito Home system (AMHS) were placed at each level of Block A, B, C and D of 17th College, UPM. The eggs laid by Aedes mosquito on the tissues inside the ovitrap were counted manually and via ‘AedesTech’ automated counting application. Monthly temperature and rainfall data from November 2018 until April 2019 were obtained from Malaysian Meteorological Department. Results: Temperature was inversely correlated to Aedes mosquito eggs count and ovitrap index. Rainfall was directly correlated to Aedes population as the number of mosquito eggs and ovitrap index were high in months recording high rainfall. The number of eggs count from ‘AedesTech’ Mobile App Version 5.9 (M=143) was significantly higher than the numbers from manual counting (M=35) indicating the ‘AedesTech’ auto-count is inaccurate. Conclusion: Temperature and rainfall have an influence on the Aedes mosquito population in the 17th College, UPM. The ‘AedesTech’ Mobile App Version 5.9 has low accuracy and therefore needs to be upgraded.